Website And Videography Training as An Online Marketing Media on Wisata Edukasi Inspirasi Preneurship Al Mumtaz (WEIPA) - Adi Nur Isnawan (FEBI UIN Sunan Kalijaga Yogyakarta, 2022)
In general, Pesantren are educational institutions that focus on religious knowledge and general knowledge as the focus of learning. But it's different from the Pesantren in Gunung Kidul, Yogyakarta, which implements business education in it. This made the Pesantren the first Pesantren in Yogyakarta based on pre-employment. This is a challenge in itself because in order to market the products in it, various special strategies are needed in an era of intense business competition. In an era that is all internet like now, only with internet, computers and smartphones can be used as a tool to publish promotional activities for Wisata Edukasi Inspirasi Preneurship Al-Mumtaz (WEIPA) products. In making videos on how to make attractive advertisements with just a smartphone and then publishing them on social media, promotional activities can be carried out anywhere and anytime easily. Then create a website, which is about how to use and manage it optimally to support and improve product promotion capabilities. This service has a target of increasing the ability of WEIPA administrators and students in utilizing technology as an efficient medium in driving economic factors and not forgetting religious knowledge as their priority. Keywords: Videograhy, Website, Marketing